2016
DOI: 10.1016/j.jcrimjus.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Escape from violence: What reduces the enduring consequences of adolescent gang affiliation?

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 71 publications
(99 reference statements)
1
16
0
Order By: Relevance
“…Intervention and prevention programs should target the modification of youths’ violent attitudes through early identification of students with low self-esteem and control, and enhancement of self-efficacy in problem-solving without resorting to aggression. Such programs should strengthen the youths’ coping skills that help them to resist negative peer influence, and support the development of a harmonious family environment and positive parenting styles [ 16 , 29 , 31 , 46 , 73 ]. To change the negative self-image, rebuilding of positive self-identity would prevent them from going astray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention and prevention programs should target the modification of youths’ violent attitudes through early identification of students with low self-esteem and control, and enhancement of self-efficacy in problem-solving without resorting to aggression. Such programs should strengthen the youths’ coping skills that help them to resist negative peer influence, and support the development of a harmonious family environment and positive parenting styles [ 16 , 29 , 31 , 46 , 73 ]. To change the negative self-image, rebuilding of positive self-identity would prevent them from going astray.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increased relational aggression has been shown to be associated with more harsh and uninvolved parenting. In these studies, interestingly, paternal but not maternal psychologically controlling parenting was positively related to relational aggression [ 22 , 29 , 30 , 31 ]. Similarly, another study found that only attachment to the father, and not to the mother, was predictive of youth aggressiveness [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parental support has utility for moderating the link between low self-control and deviance (Higgins & Boyd, 2008). Perception of support, in particular parental support, also moderates the relationship between associating with deviant friends and delinquency and drug use (Allen, Chango, Szwedo, Schad, & Marston, 2012; Dong & Krohn, 2016; Frauenglass, Routh, Pantin, & Mason, 1997; Poole & Regoli, 1979). Although Meadows (2007) reported that peer support was positively related to offending, Scarpa and Haden (2006) did find that perceived friend support moderates the impact of violent victimization on aggression.…”
Section: Social Support and Crimementioning
confidence: 99%
“…Networks of social support create a nurturing environment that provides acceptance and a sense of belonging and self-worth, and supply physical and human capital needed to refrain from violence and enhance prosocial modeling. In addition, social support creates the context in which informal and formal social control can be effectively realized (3739). At a community level, enhancing community organization through social cohesion and shared expectations for action, and developing informal mechanisms to mediate conflict and assist youth in making sense of the violent event is a worthwhile strategy (15).…”
Section: Discussionmentioning
confidence: 99%